THE EXAMINATION OF URINALYSIS PROFILES OF PREGNANT WOMEN AND TODDLER AS AN EFFORTS OF SCREENING THE POTENTIAL OCCURRENCE OF STUNTING INCIDENTS AND LOW BIRTH WEIGHT BABIES IN PENJARINGAN FLATS, RUNGKUT DISTRICT, SURABAYA - Ratna Wahyuni; taufiqurrahman sidqi; anita kurniati; Ajrina, Amalia (Universitas Airlangga, 2024)
Penjaringan Sari Flats is a solution implemented by the Surabaya City Government to overcome the limited housing in Surabaya. Due to the high number of residents , Penjaringan Sari Flats have a rapid and spread infectious rate. One of the impacts of infectious diseases that may be experienced by pregnant women and also children under five aged is low birth weight (LBW) babies and stunting. One solution to reduce the number of stunting and LBW that can be done is screening at early conditions of infection in pregnant women and toddler using the urine examination method (urinalysis). In examining a urine sample which is examined using the dipstick method (urinalysis using strips), 11 parameters can be read. Three of the eleven dipstick parameters (nitrite, leukocytes, and protein) were stated to be sufficient to screen a patient's initial infection profile. Participants in this community service activity are residents of Penjaringan Sari flats who are female, pregnant, and/or small children aged up to 5 years. The first stage carried out was the introduction of this program and activity plan to the Head of Penjaringan Sari Subdistrict. Data collection on the number of pregnant women and toddlers in Penjaringan Sari Village using observational methods. Data collection was carried out personally by the Head of Community Service accompanied by local women community. The number of pregnant women is 40 and toddlers are 60 as of August 2023. The results of urine sample examinations from 74 patients from residents of Penjaringan Sari Subdistrict are divided into two different categories: pregnant women and toddlers. In the category of pregnant women, around 90% of patients had positive leukocyte results, 60% had proteinuria, and 10% showed positive urine nitrite. In the second group, namely toddlers, the results showed that around 58.13% showed positive leukocytes, around 16.27% experienced proteinuria, and 4.65% of toddler patients had positive nitrite values.